Behaviour Of Cold-Formed Steel Built-Up Square Battened Columns Composed of Different Spacing of Chord and Battened Plate - Mohd Yazid, Muhammad Adeed Amzar; Jamaluddin, Norwati; Z. Mohd Jaini (Journal of Structural Monitoring and Built Environment, 2025)
This study investigates square hollow sections (SHS) in built-up cold-formed steel (CFS) battened columns, aiming to assess structural performance and the impact of varied spacing configurations between chords and battened plates. Four configurations were tested under axial compression to evaluate differences in load-carrying capacity, deformation, and buckling behavior. Experimental results revealed that specimens with narrower chord and batten spacing exhibited higher stiffness and load capacity, while wider spacing led to earlier onset of buckling and greater lateral displacement. Notably, the configuration with 50 mm chords and 300 mm batten spacing achieved the highest ultimate load of approximately 590 kN, demonstrating superior axial performance. Load-strain and lateral displacement patterns confirmed that reduced spacing enhanced stability and delayed buckling failure. These findings provide actionable insights into optimizing the design of CFS battened columns for enhanced structural efficiency and reliability in engineering applications.